PROPOSAL OF AN ALTERNATIVE FOR ADEQUATE INCLUSION OF ASTHMATIC CHILDREN IN PHYSICAL REHABILITATION AT THE AQUA LIFE GYMNASIUM IN THE FEDERAL DISTRICT, MEXICO. (Fiep Bulletin - online, 2013)
Asthma is a frequently found illness among populations in Mexico. Many know it and suffer from it. It is a chronic condition and no effective or definitive treatment has been discovered to cure all patients. Asthmatic children in ages between six and eight go to the Aqua Life gymnasium and are excluded by teachers of the center from the sports activities, because they do not know alternative physical activities that can satisfy the needs of those children. In the following research, our objective was to design alternative physical exercises that help include asthmatic children from six to eight years of age in sports activities at the Aqua Life Gymnasium. For this purpose, we used theoretical and empirical methods. Those empirical were the Historic-Logic method, the Analysis-Synthesis method, and among those theoretical we included a survey to the teachers to determine the current state at the gymnasium, regarding knowledge about the illness, the need of alternative physical exercises and the teacher's motivation and willingness to participate. The diagnosis revealed that the majority of the teachers had very limited knowledge about the illness, the need of alternative physical exercises to include asthmatic children in sports activities, and that there was a great motivation to apply them and there was willingness to put them into practice.